Synchronous Study of Ferroresonance and Inrush Current Phenomena and their Related Reasons in Ground Power Networks - Akrami, Amin; Ghaderi, Mohammad; Ghadi, Saeed (Electrical, Control and Communication Engineering, 2010)
Energizing the power transformers usually results in flowing very high inrush currents. This harmful current can be minimized using controlled switching and considering the value of residual flux. But nowadays, developing the ground power networks results in high increment of ferroresonance phenomenon occurrence due to the line' capacitance reactance and nonlinear inductive reactance of power transformer's core. In this study, these transient phenomena and their cause have studied synchronously.